2019
DOI: 10.3389/fpsyg.2019.00790
|View full text |Cite
|
Sign up to set email alerts
|

The Not-So-Dark Side of Materialism: Can Public Versus Private Contexts Make Materialists Less Eco-Unfriendly?

Abstract: Materialism, a way of life characterized by pursuing possessions, image, and status, has always been looked upon as self-interested and unkind. Previous studies have widely verified that materialism has a negative impact on individuals’ pro-environmental behaviors. The present research focused on whether the public (versus private) nature of a decision context will make materialists behave in more eco-friendly ways. In Study 1, the behavioral decision context (public vs. private) was manipulated to examine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…However, when the shopping context was public (at a grocery store), priming status motives increased the attractiveness of green products over non‐green products (Griskevicius et al, 2010). Similarly, priming materialism caused participants to show more greed and engage in less sustainable behaviors, consistent with Sheldon and McGregor (2000), but the effect was eliminated when participants' behaviors were public (made in the presence of an experimenter; Wang et al, 2019).…”
Section: Consequences Of Materialismsupporting
confidence: 56%
“…However, when the shopping context was public (at a grocery store), priming status motives increased the attractiveness of green products over non‐green products (Griskevicius et al, 2010). Similarly, priming materialism caused participants to show more greed and engage in less sustainable behaviors, consistent with Sheldon and McGregor (2000), but the effect was eliminated when participants' behaviors were public (made in the presence of an experimenter; Wang et al, 2019).…”
Section: Consequences Of Materialismsupporting
confidence: 56%
“…Research reveals that group situations have an important impact on consumption decisions. Some studies also found that consumers prefer to seek diversity in group buying situations (Ratner and Kahn, 2002;Wang et al, 2019) are more likely to make impulsive purchasing decisions and engage in symbolic buying behaviour, and cover up their moral hypocrite (Caviola and Faulm€ uller, 2014;L€ onnqvist, 2014). This is mainly since consumers' purchasing behaviour may be noticed by other individuals in a group situation.…”
Section: Purchase Situation Face Consciousness and Purchase Intention...mentioning
confidence: 99%
“…From this base logic, organic food consumption could be seen as similar to luxury and conspicuous consumption in terms of its capacity to bring about a good reputation and help consumers gain face. However, the former reflects the value of moral quality, while the latter reflects the value of economic status (Wang et al , 2019). Hence, the aim of the study is to test the relationship between face consciousness and purchase intention of organic food.…”
Section: Introductionmentioning
confidence: 99%
“…Although the latest data shows consistent slow decrease in materialist values and increase of post-materialist values in Lithuania, materialist values remain dominant (Inglehart, 2018). Materialistic values can indeed inhibit pro-environmental actions (Wang et al, 2019), therefore, the question is whether there is a relationship between environmental considerations and pro-environmental behavior in Lithuania.…”
Section: Introductionmentioning
confidence: 99%